“Lawan” Orang Yehuda Dan Benyamin: Sebuah Tinjauan Terhadap Teks Ezra 4:1-3 - Wijaya, Jonathan (Sekolah Tinggi Teologi Aletheia, 2024)
Abstract:Inevitably, the author of the book of Ezra did not write without a reason or agenda. Because it is clear that the writing of the book of Ezra is historiographic, this means that the writer of the book of Ezra had a purpose when he wrote and identified the people who wanted to help the tribes of Judah and Benjamin (from the land of exile) in the process of building the Temple of God as